1978
DOI: 10.1111/j.1533-8525.1978.tb01174.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nonconsequences of Objective and Subjective Status Inconsistency: Requiem for a Moribund Concept

Abstract: Though long suggested, subjective indicators of status inconsistency have seen little empirical use. Data from a sample survey with controls for additive status variables are used to compare objective and subjective status inconsistency with these conclusions: (1) Individuals in an "objective" state of educational-occupational inconsistency are no more likely to feel inconsistent than those whose objective statuses are aligned.(2) When considered in conjunction with vertical status dimensions, neither objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, debate between "objectivists" and "subjectivists" is by no means limited to the concept of alienation. is, indeed, similar to that of studies of status inconsistency (see, for example, Blocker and Riedesel 1978), power (e.g., Aberback 1977and Klorman 1978 and in applied areas such as health (Wethington 1986). It may well prove more fruitful, then, to investigate the relationships between structural (objective) and social psychological (subjective) conditions than to continue the intellectual exercise of debating the relative merits of each approach.…”
Section: Statement Of the Problemmentioning
confidence: 76%
“…However, debate between "objectivists" and "subjectivists" is by no means limited to the concept of alienation. is, indeed, similar to that of studies of status inconsistency (see, for example, Blocker and Riedesel 1978), power (e.g., Aberback 1977and Klorman 1978 and in applied areas such as health (Wethington 1986). It may well prove more fruitful, then, to investigate the relationships between structural (objective) and social psychological (subjective) conditions than to continue the intellectual exercise of debating the relative merits of each approach.…”
Section: Statement Of the Problemmentioning
confidence: 76%
“…Is status inconsistency indeed a moribund concept (Blocker & Riedesel 1978a)? Or should it be buried at one place, the macro level, and resurrected at another, the micro environment (see also Stryker & Macke 1978: 84)?…”
Section: Resultsmentioning
confidence: 99%
“…Even though Blocker and Riedesel (1978a) claim that there is virtually no relationship between measures of objective and subjective status inconsistency (cf. also Starnes & Singleton 1977), contrary to an earlier finding of Baer et al (1976) which they criticize, the measurement of status inconsistency as felt by the respective individual ("subjective status inconsistency") is a necessary requirement if any progress in status inconsistency research is to be achieved at all.…”
Section: Subjective Vs Objective Status Inconsistencymentioning
confidence: 99%
“…On the assumption that status discontent "refers as much to a state of mind as to an objectively definable condition" (Wolfinger et aL, 1969: 34), scholars have distinguished subjective or "felt" discontent with status attainment from "objective" structural positions. Stratification research has revealed such glaring gaps between fact and perception that "objective" social location can no longer be accepted as a reliable proxy for status discontent (Blocker & Riedesel, 1978;Starnes & Singleton, 1977). Rather, status discontent should be treated as an attitudinal property exhibited in varying degrees by persons at all levels of the social structure.…”
Section: Status Discontent As An Explanatory Variablementioning
confidence: 99%